2017
DOI: 10.1108/md-08-2016-0546
|View full text |Cite
|
Sign up to set email alerts
|

Distressed Chinese firm prediction with discretized data

Abstract: Purpose The authors develop a framework to build an early warning mechanism in detecting financial deterioration of Chinese companies. Many studies in the financial distress and bankruptcy prediction literature rarely do they examine the impact of pre-processing financial indicators on the prediction performance. The purpose of this paper is to address this shortcoming. Design/methodology/approach The proposed framework is evaluated by using both original and discretized data, and a least absolute shrinkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 81 publications
2
15
0
Order By: Relevance
“…Return on equity (ROE) measures the performance of shareholders during the year. It is the ratio of net income to average net equity (Geng et al , 2015; Huang et al , 2017). Higher the ROE for the company, the more income for shareholders, as it reflects the bottom-line measure of performance (Lieu et al , 2008; Ross et al , 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Return on equity (ROE) measures the performance of shareholders during the year. It is the ratio of net income to average net equity (Geng et al , 2015; Huang et al , 2017). Higher the ROE for the company, the more income for shareholders, as it reflects the bottom-line measure of performance (Lieu et al , 2008; Ross et al , 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Sermpinis et al [35] found that LASSO can significantly improve prediction performance. Huang et al [36] employed LASSO to select financial ratios and build parsimonious models based on these ratios to increase interpretability of a model. Chang et al [32] used LASSO to discover the un-revisit intension factors of hotels.…”
Section: Feature Selection With Lassomentioning
confidence: 99%
“…Many feature selection methods have been well-developed. Among them, least absolute shrinkage and selection operator (LASSO) has been widely and successfully applied in many domains, such as unrevisit intension factors discovery [32], fraud risk detection [33], bankruptcy prediction [34], power prediction [35], and financial ratio selection [36]. Moreover, LASSO can improve prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al [29] adopted LASSO method to screen model variables and found that accounting characteristics had stronger predictive ability than market characteristics. Huang et al [30] also use LASSO technology to sort the information content of each financial indicator, so as to improve the interpretability of the financial distress model.…”
Section: Related Workmentioning
confidence: 99%